2010
DOI: 10.1159/000320699
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topology Analysis of the Escherichia coli Aromatic Amino Acid Efflux Protein YddG

Abstract: YddG is an inner membrane protein (IMP) that exports aromatic amino acids in Escherichia coli. Topology models of YddG produced by sequence-based analysis in silico have predicted the presence of 9 or 10 potential transmembrane segments. To experimentally analyze the membrane topology of YddG, we used randomly created fusions to β-lactamase (BlaM) as a reporter. The selection of such fusions under 50 µg/ml of ampicillin had to fit with the periplasmic location of the BlaM domain. Five periplasmic loops of YddG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Importantly, we observed that amino acids, secreted chiefly by S. cerevisiae , but also in a substantial number of simulations by S. enterica , K. pneumoniae , and E. coli , were among the most highly-exchanged costless metabolites. This phenomenon has been previously documented in relation to overflow metabolism in S. cerevisiae 31 and E. coli 32,33 , as well as in yeast-bacteria symbioses 34,35 , and account for exchange in over 10 4 simulations with and without oxygen in our study. This high prevalence of exchange underscores the metabolic utility of these secreted byproducts, particularly when contrasted with patterns of secretion in which the most commonly released metabolites were of low or no metabolic utility to a partner organism (e.g.…”
Section: Resultssupporting
confidence: 81%
“…Importantly, we observed that amino acids, secreted chiefly by S. cerevisiae , but also in a substantial number of simulations by S. enterica , K. pneumoniae , and E. coli , were among the most highly-exchanged costless metabolites. This phenomenon has been previously documented in relation to overflow metabolism in S. cerevisiae 31 and E. coli 32,33 , as well as in yeast-bacteria symbioses 34,35 , and account for exchange in over 10 4 simulations with and without oxygen in our study. This high prevalence of exchange underscores the metabolic utility of these secreted byproducts, particularly when contrasted with patterns of secretion in which the most commonly released metabolites were of low or no metabolic utility to a partner organism (e.g.…”
Section: Resultssupporting
confidence: 81%
“…Importantly, we observed that amino acids, secreted chiefly by Saccharomyces cerevisiae , but also in a substantial number of simulations by Salmonella enterica , Klebsiella pneumoniae , and E. coli , were among the most frequently exchanged costless metabolites. This phenomenon has been previously documented in relation to overflow metabolism in S. cerevisiae 45 and E. coli 46,47 , as well as in yeast–bacteria symbioses 48,49 . This high prevalence of exchange underscores the metabolic utility of these secreted byproducts.…”
Section: Resultssupporting
confidence: 56%
“…In this experiment, donors are not expected to specifically produce the amino acid that the cocultured auxotroph requires for growth. Moreover, bacteria usually use generic transporters to import chemically similar amino acids [5557]. Thus, auxotrophic recipients may benefit not only from the one amino acid they require for growth but potentially also from utilising other amino acids that are produced by the donor.…”
Section: Resultsmentioning
confidence: 99%